2010
DOI: 10.2174/1874091x01004010100
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Between Nitric Oxide and Superoxide Anion Radical During Progressive Exercise in Elite Soccer Players

Abstract: Background:Exercise increases production of reactive oxygen and nitrogen species (RONS) via several mechanisms. Inter alia, increased blood flow during exercise exposes endothelial cells to shear stress, resulting in increased nitric oxide (NO) production. Increased oxygen consumption or hypoxia during exercise induces increased production of superoxide anion radical (O2-). Objective:This study investigates the effects of maximal progressive treadmill exercise test on time-course of peripheral blood NO and O2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 56 publications
0
11
0
2
Order By: Relevance
“…6,18,19,25 Many factors may have influenced this outcome, including the study design, small number of subjects, and NO measurement methods. Nonetheless, LMS, a value representing aerobic endurance, and BSNO levels were found to be greater in the AeG than in the AnG and CG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,18,19,25 Many factors may have influenced this outcome, including the study design, small number of subjects, and NO measurement methods. Nonetheless, LMS, a value representing aerobic endurance, and BSNO levels were found to be greater in the AeG than in the AnG and CG.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been found that there are relationships between aerobic power (VO 2 max) and BSNO levels and aerobic exercise increases basal blood NO levels. 1,18,19 However, the relationships between anaerobic exercise and BSNO remain largely unclear.…”
Section: ö öZ Ze Et T Amentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that investigated the effects of acute exercise on • NO production yielded various results. Some studies reported • NO increase with exercise, some reported no change in • NO production and some reported a decrease in • NO production with exercise (Jungersten et al, 1997;Rassaf et al, 2007;Allen et al, 2006;Allen et al, 2009;Djordjevic et al, 2010a;Poveda et al, 1997;Djordjevic et al, 2010b;Jakovljevic et al, 2011;Cubrilo et al, 2011). Those differences are probably due to different protocols, i.e.…”
Section: Comparison Of Blood Pro/antioxidant Levels Before and After mentioning
confidence: 99%
“…During exercise, the several-fold rise of energetic needs and oxygen consumption may induce increased production of reactive oxygen and nitrogen species (RONS) and possible disruption of the redox state, i.e., oxidative stress [1]. The first study of the relationship between exercise and oxidative stress was performed in 1978 by Dillard and colleagues [2] and demonstrated that acute aerobic exercise increases lipid peroxidation, which may be mediated by vitamin E consumption.…”
Section: Introductionmentioning
confidence: 99%